Family implementation of home-based early intervention programs for children with pervasive developmental disorders - Mejia, Ria H. (2009)
This exploratory and descriptive study investigates the process of implementation of home-based early intervention programs by families of children with PDD and the factors that influences the facilitation. A two-part case study consisting of interviews and observation was used to gather data. Findings indicate that family interventionist, most likely a female, is usually able to facilitate various learning activities to a child with PDD using appropriate general instructional approaches, teaching modes, and specific instructional strategies to assist or correct the child. Family interventionists, professionals, HBEIPs, learning environment, and the child are the factors that influence the facilitation of learning activities at home.
Thesis (M.A. Special Education)--University of the Philippines, Diliman.
Keywords: Home-based family services -- Philippines -- Manila Metropolitan Area; Home-based mental health services -- Philippines -- Manila Metropolitan Area; Developmentally disabled children -- Services for -- Philippines -- Manila Metropolitan Area; Children with disabilities -- Philippines -- Manila Metropolitan Area